Impact of hormone applications on ripening-related metabolites in Gewürztraminer grapes (Vitis vinifera L.): The key role of jasmonates in terpene modulation. (15th September 2022) - Wang, Junfang; VanderWeide, Joshua; Yan, Yifan; Tindjau, Ricco; Pico, Joana; Deluc, Laurent; Zandberg, Wesley F.; Castellarin, Simone D.
Highlights: The effects of hormone applications on grape terpenes were tested. Free and bound terpenes were increased by jasmonate applications. Jasmonates increased the expression of terpene genes . Increases in terpenes were not related to sugar or anthocyanin increases. ABA, ethylene, and auxins did not consistently affect terpene concentrations. Methyl jasmonate increased auxin levels and reduced sugar levels. Abstract: Terpenes play a formative role in grape and wine flavor, particularly for high-terpenic cultivars. Differences in terpene profiles influence grape varietal character and vintage quality. Little is known about the endogenous factors controlling terpene biosynthesis in grape. Through multiple experiments, six hormones (abscisic acid, ABA; ethylene, ETH; jasmonic acid, JA; methyl jasmonate, MeJA; indole-3-acetic acid, IAA; 1-naphthaleneacetic acid, NAA) that either promote or repress ripening were applied to Gewürztraminer clusters near veraison to gauge their effect on ripening and terpene biosynthesis. Jasmonates (JA, MeJA) increased terpene concentrations and the expression of terpene genes in grapes. Such increases were not associated to increases of other ripening-related metabolites such as sugars or anthocyanins. MeJA also affected the expression of several hormone related genes, increased IAA levels, and reduced sugar and anthocyanin concentration in grapes. This research provides novel insights into terpene regulation by ripening-related hormones and jasmonates in grapes.